2000
DOI: 10.1097/00003246-200007000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil deformability in patients with sepsis, septic shock, and adult respiratory distress syndrome

Abstract: The entire neutrophil population is less deformable in SP, SS, and ARDS patients. The decreased deformability of passive neutrophils suggests that a direct mechanism involving actin polymerization, distinct from cell activation, is involved. These observations may be important in the mechanism of impaired vascular flow in patients with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 19 publications
2
56
0
1
Order By: Relevance
“…I t has been reported that neutrophils are activated in patients with systemic inflammatory response syndrome (SIRS) 1,2 that is associated with sepsis, [3][4][5] severe trauma, 6 and acute lung injury (ALI). 5,7,8 Under these conditions, activated neutrophils are sequestered, 9 produce inflammatory products 10 -12 such as neutrophil elastase (NE), 13 and show decreased deformability.…”
mentioning
confidence: 99%
“…I t has been reported that neutrophils are activated in patients with systemic inflammatory response syndrome (SIRS) 1,2 that is associated with sepsis, [3][4][5] severe trauma, 6 and acute lung injury (ALI). 5,7,8 Under these conditions, activated neutrophils are sequestered, 9 produce inflammatory products 10 -12 such as neutrophil elastase (NE), 13 and show decreased deformability.…”
mentioning
confidence: 99%
“…When neutrophils are activated, the increase of intracellular free calcium level and activation of F-actin make the neutrophils stiff. Skoutelis et al [15] have demonstrated that neutrophil deformability was significantly decreased in patients with ARDS. There are several studies reporting that selectins might be involved in cell activation [16].…”
Section: Discussionmentioning
confidence: 98%
“…The smaller increase in cell volume of activated PMNs observed in our study may be explained by exclusion of activated PMNs with irregular shapes from the volume analysis. Skoutelis et al [31] showed that deformability of passive PMNs of patients with septicemia was decreased compared with passive PMNs of healthy controls. They used micropipettes with internal diameters of 5 mm for aspiration of the whole cell.…”
Section: Discussionmentioning
confidence: 99%